2020
DOI: 10.1093/ndt/gfz287
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the implementation of an assisted peritoneal dialysis service on peritoneal dialysis initiation

Abstract: Background There is limited information available on the impact that provision of an assisted peritoneal dialysis (PD) service has on the initiation of PD. The aim of this study was to assess this impact in a centre following initiation of assisted PD in 2011. Methods This retrospective, single-centre study analysed 1576 patients incident to renal replacement therapies (RRTs) between January 2002 and 2017. Adjusted Cox regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 53 publications
2
28
0
1
Order By: Relevance
“…Patients in the assisted PD group were older, more likely to be female, more prevalent in diabetes and cardiovascular disease and carried a heavier burden of comorbid diseases than patients in the self-care PD group. Similar to our study, Boyer et al showed that patients starting PD with assistance were older than those starting unassisted (70.0 (61.5-78.3) vs 58.7 (43.8-69.2) years) 12 . In another study from France, Lobbedez et al reported that assisted PD patients were older (74 ± 10.4 vs 52 ± 18.6 years, P < 0.001) and presented more comorbidity (CCI 7 ± 2.5 vs 4.3 ± 2.4, P < 0.05) compared with selfcare patients 22 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Patients in the assisted PD group were older, more likely to be female, more prevalent in diabetes and cardiovascular disease and carried a heavier burden of comorbid diseases than patients in the self-care PD group. Similar to our study, Boyer et al showed that patients starting PD with assistance were older than those starting unassisted (70.0 (61.5-78.3) vs 58.7 (43.8-69.2) years) 12 . In another study from France, Lobbedez et al reported that assisted PD patients were older (74 ± 10.4 vs 52 ± 18.6 years, P < 0.001) and presented more comorbidity (CCI 7 ± 2.5 vs 4.3 ± 2.4, P < 0.05) compared with selfcare patients 22 .…”
Section: Discussionsupporting
confidence: 91%
“…Assisted PD is de ned as PD treatment performed at the patient's home and with the assistance of a family member, a partner, a community nurse or a healthcare technician 11 . As a feasible option for patients who cannot perform their own PD exchanges, assisted PD have been developed in many countries with the aim of overcoming barriers in older and nonself-su cient patients, and some studies suggested that the use of assisted PD could increase the utilization of PD patients among older [12][13][14] . However, whether assisted PD achieved similar outcomes to self-care peritoneal dialysis still remained controversial 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Our study also shows that, due to a decline in family assistance, assisted PD currently relies mainly on nurse assistance. It has been demonstrated that widespread adoption of assisted PD services would significantly increase PD initiation [ 46 ]. Although there are added costs to nurse-assisted PD, a Netherlands study demonstrated that it is a cost-effective option [ 47 ] in elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…This is largely because many patients who could benefit from PD experience physical and/or cognitive barriers to managing dialysis by themselves [8], and also lack the supports needed to compensate. Indeed, providing home supports to these patients has increased uptake of PD is some areas, like the UK and Canada [16, 17]. However, in other places, like France, it has not [12].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile in France, where there exists a well-funded aPD program, the median age of patients on PD is 71 years [14]. PD uptake improved with a HR of 1.13 (95% CI 1.05–1.21) for increased rate of CAPD utilization for nurse-assisted PD patients [16]. This relationship is corroborated in another study looking at 134 incident ESRD patients in Ontario, 80% of whom had at least 1 personal barrier to self-care PD [17].…”
Section: Assisted Peritoneal Dialysismentioning
confidence: 99%